Changes in Soil Fertility in Soils of Srigangangar District of Rajasthan - Kumar, Vinod; Fakhruddin, Mohd.; Seth, S P (Annals of Arid Zone, 2016)
Based on the analysis of 22907 surface soil samples received in soil testing laboratory, Srigauganagar, during June J966 to June 1971, nutrient index for organic carbon, available P205 and available K2O was calculated to assess the changes in soil fertility in soils of Srigaoganagar district, It has been observed that the nutrient index values for organic carbon 2nd available P205 has gone up i. e. from 1.23 and 1.83 to 1.29 and 2.02 respectively from 1966 to 197J while the nutrient index for available K2Odecreased from 2.25 to 1.97. With respect to pH there was increase of 4.93 per cent samples in pH range between 8.0 to 8.5 The values for electrical conductivity remained unaffected. Tentative fertiliser recommendations based on Dresent fertility status of soils were also formulated for some important crops of the region